(untitled) (Journal of Libya for geographical studies, 2024)
The Municipality of Misrata witnessed a remarkable population development, which was reflected in urban expansion and the increase in housing need at the expense of agricultural land areas and sand dunes in the region, and due to the seriousness of this problem and the negative consequences that result from it, this study aimed at knowing the population growth in the Misrata region and its role in changing the areas of sand dunes and monitoring this change by drawing the results of the analysis of judicial views (5 Landsat - 1990 TM) and (8 Landsat - 2021 OLI) using GIS technology and sensing After that, the study found a change in the area of sand dunes in the Misrata region by (-21.8 km²), and the urban area at the expense of neighboring lands, whether sand dunes or agriculture, increased by about (129.28 km²) during the years 1990 and 2021. The importance of this study comes in the search for the relationship between population growth on the one hand and the importance of sand dunes as an environmental habitat for many living organisms and an important resource for humans and their activities on the other hand.